2018
DOI: 10.1038/s41598-018-23149-0
|View full text |Cite
|
Sign up to set email alerts
|

Laser speckle flowgraphy derived characteristics of optic nerve head perfusion in normal tension glaucoma and healthy individuals: a Pilot study

Abstract: The purpose of this prospective, case control study was to investigate the differences in optic nerve head blood flow measured with Laser Speckle Flowgraphy (LSFG) between Caucasian patients with normal tension glaucoma and healthy subjects. It included 20 eyes from 20 Caucasian patients with diagnosis of normal tension glaucoma and 20 eyes from age- and sex-matched healthy individuals. In the glaucoma group the antiglaucomatous therapy was paused 3 weeks prior to the investigations. Measurement of optic nerve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 28 publications
1
26
0
3
Order By: Relevance
“…An advantage of LSF, compared with OCT-A, is the possibility to measure the waveform of the pulsatile signal, which can be changed in diseased eyes. This was shown for patients with glaucoma [ 28 , 31 ].…”
Section: Introductionmentioning
confidence: 72%
See 2 more Smart Citations
“…An advantage of LSF, compared with OCT-A, is the possibility to measure the waveform of the pulsatile signal, which can be changed in diseased eyes. This was shown for patients with glaucoma [ 28 , 31 ].…”
Section: Introductionmentioning
confidence: 72%
“…Shiga et al [ 31 ] described a delay in the peak of the MBR waveform, a flattened waveform, and reduced MBR amplitude for normal tension glaucoma (NTG) subjects in the ONH capillary area only. Mursch-Edlmayr et al [ 28 ] found a reduced blood flow in the vessels supplying the retina assessed by MBR from ONH in NTG subjects. They also evaluated the shape of the MBR curve using several specific parameters and found a flatter waveform for NTG subjects, which means a lower MBR avg and a lower flow acceleration index.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, many studies have compared the MT between normal and glaucoma eyes or glaucoma eyes with different stages of the disease. 9 17 With regard to MV, in vitro experiments and comparison with laser Doppler velocimetry indicate that MV is a quantitative parameter of blood velocity in the large retinal vessels at the ONH. 18 20 …”
Section: Introductionmentioning
confidence: 99%
“…First, blood flow monitoring is important to evidence retinal hypoperfusion inherent to many ocular diseases. For example laser speckle flowgraphy can measure abnormal perfusion in some types of glaucoma [5,6], and Doppler ultrasound is able to detect decrease of the ocular circulation [7]. Going further into the study of blood flow dynamics, a time-resolved analysis of blood flow changes contains a wealth of information as the arterial waveform profile is influenced by the arterial compliance and peripheral resistance [8][9][10].…”
Section: Introductionmentioning
confidence: 99%